СУДОВО-ҐРУНТОЗНАВЧА ЕКСПЕРТИЗА ПІСЧАНИХ ҐРУНТІВ - Khlestkova, O. O. (Теорія та практика судової експертизи і криміналістики, 2016)
The expert study of sandy soil is becoming increasingly relevant due to the growing number of criminal cases involving illegal extraction ofsand as a mineral. The article offers a methods of studying sandy soils, it consists of determining a morphological properties, qualitative grain (granulometric) composition, the composition of minerals and the properties of sand grains judging by their exterior properties. The article points out that the primary element of studying sands and sandy soils is obtaining representative samples for analysis. It is conditioned, firstly, by a highly non-homogeneous nature of these objects and, secondly, by such property of soil as inconsistency, hence porosity. In addition, when sandy soils get on the carrying object, like clothes, and then the soil is taken for study, the initial properties of these objects change resulting from partial loss of fine humus and clay fraction that is stuck on the fabric of the item. At the same time a big (sandy) fraction may crumble down. The article also deals with the issues of classifying the existing sizes of granulometric fractions ofminerals in geology, soil studies and industry.